The Effect of Leunca Fruit (Solanum nigrum Linn) Infusion in Inhibiting the Increase of Serum Glutamate Pyruvate Transaminase Level in CCL4 Induced Hepatitis Wistar Rats - Kuswinarti Kuswinarti; Syifa Karmani; Coriejati Rita (Althea Medical Journal, 2019)
Background: Hepatitis may cause liver cell damage due to the oxidation processes and can be inhibited by antioxidant components. Antioxidant acts as hepatoprotector by slowing down the oxidation process. Leunca fruits (Solanum nigrum Linn) contain antioxidants such as vitamin C and flavonoid. This study aimed to explore the effect of Leunca fruit infusion to inhibit the increase of serum Glutamate Pyruvate Transaminase (SGPT) level in Wistar rats’ blood.Methods: This was an experimental study using male Wistar rats, conducted in the Animal Laboratory, Department of Pharmacology and Therapy, Faculty of Medicine, Universitas Padjadjaran between September−October 2012. The Hepatitis rats model was induced with carbon tetrachloride (CCl4) in 10% paraffin intraperitoneally as much as 8 mL/kgBW on day 8th. A 3 mL of leunca fruit infusion was given with a concentration of 22.5 g, 45 g, and 90 g per 100 mL, respectively. On the 10th day, serum was taken and SGPT was examined. Only food and distilled water were given to the negative control group. The result was analyzed by using a Kruskal-Wallis non-parametric test, followed by Mann-Whitney post hoc.Results: There was a significant difference between the negative control and hepatitis positive control group (p=0.009), indicating that the induction was successful. The dose 90 g/100 mL leunca had a significant different in SGPT concentration (p=0.047), suggesting that leunca fruit infusion had a significant effect on reduced SGPT level.Conclusions: Leunca fruit infusion has a hepatoprotective effect by inhibiting the increase of the SGPT level in CCl4 induced rats. Studies on the leunca effectiveness in human hepatitis need further exploration.